Long‐term excess risk of stroke in people with Type 2 diabetes in Sweden according to blood pressure level: a population‐based case–control study. Issue 4 (18th January 2017) - Hedén Ståhl, C.; Lind, M.; Svensson, A.‐M.; Kosiborod, M.; Gudbjörnsdottir, S.; Pivodic, A.; Clements, M.; Rosengren, A.
Abstract: Aims: To estimate the risk of stroke in people with Type 2 diabetes with different blood pressure levels compared with the risk in the general population in Sweden. Methods: This prospective case–control study included 408 076 people with Type 2 diabetes, aged ≥ 18 years, and free of prior stroke, registered in the Swedish National Diabetes Register 1998–2011. Age‐ and sex‐matched control subjects ( n = 1 913 507) without stroke from the general population were included. Stroke diagnoses were retrieved using International Classification of Disease codes from the Swedish patient and death registers. Cox hazard ratios and 95% confidence intervals (CIs) were estimated at six different blood pressure levels. Results: During a median follow‐up of 4 years, 19 548 (4.8%) people with Type 2 diabetes and 61 690 (3.2%) without diabetes were diagnosed with stroke, corresponding to an adjusted hazard ratio of 1.43 (95% CI 1.41–1.46) for people with Type 2 diabetes as a group. Compared with people without diabetes, the risk of stroke for people with Type 2 diabetes with different blood pressure levels was significantly higher, starting at blood pressure levels > 130/80 mmHg. Hazard ratios for stroke were 1.20 (95% CI 1.16–1.24), 1.47 (95% CI 1.43–1.50), and 1.97 (95% CI 1.90–2.03) for blood pressure categories of 130–139/80–89 mmHg, 140–159/90–99 mmHg and ≥ 160/≥ 100 mmHg, respectively, after adjustment for age, sex, diabetes duration, being born in Sweden, maximum education level and baseline comorbidities. Conclusions: People with Type 2 diabetes and blood pressure < 130/80 mmHg had a risk of stroke similar to that of the general population. What's new?: Type 2 diabetes and blood pressure level are well known predictors of stroke, but the risk of stroke for people with Type 2 diabetes at different blood pressure levels compared with the risk for the general population is not known. We found that people with Type 2 diabetes and blood pressure < 130/80 mmHg had a risk of any stroke similar to that of the general population. People with Type 2 diabetes and blood pressure in the range of 120–139/70–89 mmHg had a significantly lower risk of haemorrhagic stroke compared with the general population.